Alignment of magnetic particles in hydrogel matrix: A novel anisotropic magnetic hydrogels for soft robotics. (August 2021) - Bin, Li; Xu, Chanchan; Dong, Shuai; Wang, Xiaojie
Magnetic hydrogels are composed of magnetic particles and hydrogel matrix. In recent years, the magnetic hydrogels have been developed rapidly because they have shown promising applications in drug release and artificial muscle. In this paper, we proposed a study to develop novel anisotropic magnetic hydrogels and investigate their mechanical and sensing properties for possible applications in soft robotics. In preparing the anisotropic magnetic hydrogels, the polyacrylamide (PAAm) hydrogel is chosen as a model hydrogel because of its popular application in soft electronics and ionic conductors. A method of free radicals copolymerization is employed to fill (polyacrylic acid/acrylamide) polymers in preparing anisotropic hydrogels under the magnetic field. Unlike most of the previous studies which incorporated magnetic nanoparticles into hydrogels, we mixed the micro-size carbonyl iron particles (CIPs) with the hydrogel and cured them under a magnetic field to form anisotropic structures within its crosslinking polymer chains. The particles and formed particle chains will not only improve the mechanical properties of the hydrogels but also provide sensing function as the electrical resistance changed from mechanical deformation referred to piezoresistivity. We experimentally evaluated the magnetorheological and the piezoresistive behaviors of the magnetic hydrogels, and demonstrated their potential use in soft robots as flexible touch sensors and variable-stiffness devices.